Oral and maxillo-facial injuries in victims of political repression during the Chilean dictatorship - Silva, Jesús (Torture Journal, 2023)
Introduction: Chile was under a civil-military dictatorship during 17 years from 1973 to 1990. During that time, systematic violations to the human rights were perpetrated. Oral and maxillo-facial trauma was not an exception using different methods of torture or ill treatment by agents of state. Currently, Chile has laws and programs in the public healthcare system to carry out the rehabilitation and reparation process in victims, where the registration of the suffered damages is considered an important part of medico-legal procedures. Methods: 14 “Reports of oral and maxillo-facial damage” of tortured victims elaborated from 2016 to 2020 were analyzed, considering the alleged history of the patient, the visible effects on the oral examination and the background about the type of torture that were applied. Historical clinical records and RX exams were analyzed when available. Results: 6 ways of torture and ill-treatments that involve the maxillo-facial area were found caused by agents of state occurred during all the dictatorship period. Discussion: All of the torture techniques applied caused directly or indirectly the loss of teeth according to the patient´s story and the clinical examination, causing not only physical problems, but psychological problems to the victims.